Antibody conjugates in neuroblastoma: a step forward in precision medicine - Balla, Jihane; Siddi, Carlotta; Scherma, Maria; Fadda, Paola; Dedoni, Simona (Frontiers in Oncology, 2025)
Neuroblastoma (NB) is a pediatric cancer that often manifests in a high-risk form and is characterized by frequent relapses and resistance to conventional therapies. This underscores the urgent need for more effective and targeted treatment strategies. One promising avenue has been the identification of unique or overexpressed surface antigens on neoplastic cells, which has facilitated the development of antibody conjugates and related technologies. These include antibody-drug conjugates (ADCs) and immunotoxins (ITs), which deliver cytotoxic agents directly to tumor cells, as well as antibody-fluorophore conjugates (AFCs), which bind to surface antigens with high specificity to target malignant tumors. Additionally, radioimmunotherapy (RIT) allows the precise delivery of radioactive isotopes linked to a monoclonal antibody directly to the tumor cells. ADCs, ITs, and RIT represent a novel class of anti-cancer agents offering precision therapy with reduced systemic toxicity, enabling longer and potentially more effective treatment regimens. Meanwhile, AFCs are valuable tools in diagnostics, aiding in detecting and characterizing malignant tissues. Despite advancements in antibody conjugates for NB, significant challenges persist, including optimizing payload delivery, mitigating off-target effects, and addressing tumor heterogeneity. Future research should also prioritize refining and integrating these technologies into multimodal treatment protocols to improve outcomes for pediatric NB patients.